2016
DOI: 10.1016/j.gde.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-like behavior of chromatin

Abstract: Eukaryotic chromatin is a negatively charged long polymer composed of genomic DNA, histones, and various proteins. The charged property causes the chromatin structure to be dynamically changed. These dynamic changes are critical for genome functions such as gene expression because they directly govern the degree of DNA accessibility. Although the chromatin structure is not yet fully understood, currently increasing evidence suggests that chromatin has a dynamic liquid-like structure based on the 10-nm fiber bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 100 publications
8
103
0
2
Order By: Relevance
“…A more dynamic, liquid-like state of chromatin is currently considered ( 48 ) instead of the classical 30-nm fibers, which so far have not been observed in vivo. A dynamic, “fluid” behavior of chromatin would be fully supported by the weak nucleosome-nucleosome interaction potential measured here.…”
Section: Discussionmentioning
confidence: 99%
“…A more dynamic, liquid-like state of chromatin is currently considered ( 48 ) instead of the classical 30-nm fibers, which so far have not been observed in vivo. A dynamic, “fluid” behavior of chromatin would be fully supported by the weak nucleosome-nucleosome interaction potential measured here.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, micromechanical experiments using micropipettes have shown that mitotic chromosomes are highly elastic objects that return to their native lengths even after five-fold extensions (Marko, 2008). Compared with the interior of chromosomes, their periphery is expected to be less dense and to behave like a liquid, as has been predicted for interphase chromatin (Maeshima et al, 2016). Along these lines, an intriguing observation from an early study is that the condensin subunit SMC2 first appears at the surface of condensing chromosomes in middle prophase, and then suddenly translocates into the interior of chromosomes where axial structures are formed by late prophase (Kireeva et al, 2004) (Fig.…”
Section: Heat Repeats In Mitotic Chromosome Dynamicsmentioning
confidence: 96%
“…(31,32,70,71). Additionally, several theoretical models (72)(73)(74)(75) and computer simulations of chromatin polymer (17,34,34,61,76) have shown the broad consistency of heterogeneous copolymer melt view of chromatin with the Hi-C and single-molecule data.…”
Section: Resultsmentioning
confidence: 88%